Photochemistry in clusters and nanoparticles of atmospheric relevance - Fárník, M. (Michal); Poterya, V. (Viktoriya); Ončák, M. (Milan); Slavíček, P.; Buck, U. (2010)
Ice nanoparticles and water clusters play a key role in many processes in our atmosphere and also in astrochemistry. By the way of example, the ice particles in the polar stratospheric clouds (PSC) catalyze the reactions which lead to the ozone depletion process in the stratosphere above Antartica.